THE ANALYSIS FACTORS WHICH INFLUENCE FINANCIAL CAPITAL STRUCTURE IN BANKING COMPANY WHICH GO PUBLIC IN INDONESIA - Desky Prihandoyo Putro, 08.05.52.0162; Puspitasari, Elen (Students Journal of Accounting and Banking, 2013)
Capital is needed to build and ensure the continuity of the company, in addition to the machines resources, material as a contributing factor. Therefore, the company must determine the amount of capital required to meet or finance business and capital structure issues makes an interesting subject matter to be investigated. The factors are the structure of assets, profitabilatas, asset growth, firm size, liquidity and leverage objective of this study was to examine and analyze the evidence of the influence of asset structure, profitability, asset growth, firm size, liquidity and leverage on capital structure. Data from the observations made ââin 2007-2011. The population in this study are all banking companies that went public on the Stock Exchange. Sampling technique in this study was done by using purposive sampling and observational data obtained with as many as 85. The data used are secondary data obtained from the banking companys financial statements obtained from the Indonesian Stock Exchange (IDX) and the annual report of the year 2007-2011.The analysis technique used is multiple regression. The result of this study were indicates that the: Structure Asset, Profitability, Company Size, Liquidity and Leverage positive effect on capital structure. While Asset Growth negatively effect on capital structure,Keywords: Structure Asset, Profitability, Assets Growth, Company Size, Liquidity, and Laverage, Capital Structure.